Cerebral palsy after neonatal encephalopathy: do neonates with suspected asphyxia have worse outcomes?. (11th November 2015) - Garfinkle, Jarred; Wintermark, Pia; Shevell, Michael I; Oskoui, Maryam; ,
Abstract : Aim: We sought to investigate how brain injury and severity, and neurological subtype of cerebral palsy (CP) differed in term‐born children with CP after neonatal encephalopathy, between those with suspected birth asphyxia and those without. Method: Using the Canadian CP Registry, which included 1001 children, those with CP born at ≥36wks after moderate or severe neonatal encephalopathy, were dichotomized according to the presence or absence of suspected birth asphyxia. Gross Motor Function Classification System (GMFCS) scores, neurological subtypes, comorbidities, and magnetic resonance imaging findings were compared. Results: Of the 147 term‐born children with CP (82 males, 65 females; median age 37 months, interquartile range [IQR] 26–52.5) who after moderate or severe neonatal encephalopathy had the required outcome data, 61 (41%) met criteria for suspected birth asphyxia. They had a higher frequency of non‐ambulatory GMFCS status (odds ratio [OR] 3.4, 95% confidence interval [CI] 1.72–6.8), spastic quadriplegia (OR 2.8, 95% CI 1.4–5.6), non‐verbal communication skills impairment (OR 4.2, 95% CI 2.0–8.6), isolated deep grey matter injury (OR 4.1, 95% CI 1.8–9.5), a lower frequency of spastic hemiplegia (OR 0.17, 95% CI 0.07–0.42), focal injury (OR 0.20; 95% CI 0.04–0.93), and more comorbidities ( p =0.017) than those who did not meet criteria. Interpretation: Term‐born children who develop CP after neonatal encephalopathy with suspected birth asphyxia have a greater burden of disability than those without suspected birth asphyxia. What this paper adds: Children with cerebral palsy after neonatal encephalopathy with suspected birth asphyxia were compared to those without suspected birth asphyxia. They are three times more likely to have a non‐ambulatory Gross Motor Function Classification System status and/or spastic quadriplegia. They are four times more likely to have non‐verbal communication skills impairment. They more frequently have isolated deep grey matter injury. This article is commented on by Marret on pages118–120 of this issue.